SURFACE ELECTRONIC STATES OF METEORITIC NANODIAMONDS - Garvie L.A.J. (My University, 2006)
The C K edge of Orgueil nanodiamonds (Cδ diamonds) was acquired by electron energy-loss spectroscopy (EELS), with an energy resolution of 300 meV. The spectra show peaks at 282.5, 284.7, and 286.4 eV, which occur in the band gap below the main diamond edge and are absent from the bulk diamond spectrum. These peaks are attributed to transitions from C 1s surface core levels to unoccupied surface states, and arise from single and π-bonded dangling bonds and C-H bonds. A shoulder to the main absorption edge at 287.8 eV may correspond to hydrocarbon adsorbates. These results can be used to further our understanding of Cδ diamond structure and may reveal the presence of a fullerene-like surface. The unique surface electronic states of the Cδ diamond surfaces are expected to affect their optical properties, which are dependent on features such as extent of H coverage, particle size, and surface structure. © The Meteoritical Society, 2006.